Assessing the impact of TET2 and TET3 deletion in TCRalpha and TCRbeta repertoire in murine CD4 T cells in physiological and pathophysiological conditions - Äijö, Tarmo; Gioulbasani, Marianthi; Valenzuela, Jair Ernesto; Tsagaratou, Ageliki (Frontiers in Immunology, 2025)
Ten Eleven Translocation (TET) proteins can oxidize 5-methylcytosine to generate in sequential steps oxidized forms of cytosine: 5-hydroxymethylcytosine, 5-formylcytosine and 5-carboxylcytosine. Through their catalytic activity TET proteins promote active DNA demethylation. There are three TET proteins: TET1, TET2 and TET3. In T cells, TET2 and TET3 are more highly expressed. In the past years we have extensively analyzed the impact of TET proteins and 5-hydroxymethylcytosine in T cell development. In this report, we focus on the impact of TET proteins in the TCR alpha (α) and beta (β) repertoires in thymic CD4 single positive cells and upon migration in the periphery. Our data reveal that both wild type and Tet2/3 DKO CD4 cells in the thymus and the spleen are polyclonal. Then, we focus on Tet2/3 DKO CD4 cells that are serially transplanted in recipient mice. Our TCR sequencing data reveals that expanded Tet2/3 DKO CD4 cells are less diverse and oligoclonal. Overall, this report serves as a resource of TCRα and TCRβ repertoire in both wild type and Tet2/3 DKO murine conventional CD4 T cells and provides insights on how expanded Tet2/3 DKO CD4 cells opt for specific TCRα and β repertoires.